Speech disorders did not correlate with age at onset of Parkinson’s disease - Dias, Alice Estevo; Barbosa, Maira Tonidandel; Limongi, João Carlos Papaterra; Barbosa, Egberto Reis (Arquivos de Neuro-Psiquiatria, 2016)
Speech disorders are common manifestations of Parkinson´s disease. Objective To compare speech articulation in patients according to age at onset of the disease.Methods Fifty patients was divided into two groups: Group I consisted of 30 patients with age at onset between 40 and 55 years; Group II consisted of 20 patients with age at onset after 65 years. All patients were evaluated based on the Unified Parkinson’s Disease Rating Scale scores, Hoehn and Yahr scale and speech evaluation by perceptual and acoustical analysis.Results There was no statistically significant difference between the two groups regarding neurological involvement and speech characteristics. Correlation analysis indicated differences in speech articulation in relation to staging and axial scores of rigidity and bradykinesia for middle and late-onset.Conclusions Impairment of speech articulation did not correlate with age at onset of disease, but was positively related with disease duration and higher scores in both groups.
Keywords: Parkinson´s disease; speech articulation; dysarthria